If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(3x + -1) = 3(12x + 2) Reorder the terms: 12(-1 + 3x) = 3(12x + 2) (-1 * 12 + 3x * 12) = 3(12x + 2) (-12 + 36x) = 3(12x + 2) Reorder the terms: -12 + 36x = 3(2 + 12x) -12 + 36x = (2 * 3 + 12x * 3) -12 + 36x = (6 + 36x) Add '-36x' to each side of the equation. -12 + 36x + -36x = 6 + 36x + -36x Combine like terms: 36x + -36x = 0 -12 + 0 = 6 + 36x + -36x -12 = 6 + 36x + -36x Combine like terms: 36x + -36x = 0 -12 = 6 + 0 -12 = 6 Solving -12 = 6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 177-6x=39x+17 | | 12y^2-27=0 | | 8+5r-7=9r+9-6r | | 8x-35=25-2x | | 8-8x=133-43x | | 3x+17=13x-83 | | 7(t^2+5t-9)+t=t(7t-2)+13 | | 4t=-44 | | -7x+6=90 | | 3x+17=7x+3 | | 9x+5x-2x=0 | | 4=0.5(3x-4) | | 10x-15=-5x+30 | | 5s+11s=80 | | 115-5x=5x+15 | | 8+5y=-27 | | 3x^2-13x-16=-6 | | 0.05(x+30)-0.02(x-10)=3.2 | | -4586+y=5876 | | -9(3b+1)+(28b-2)=0 | | 5x+9(x-17)=8(9+x)+6x | | 9(2.5)-10= | | 3(2.5)+5= | | 83-4x=23x+20 | | 7-7x=82-42x | | =20+3 | | h-6j+7h+10j= | | 3.2q-3.6-4.1q=1.9q-4.8 | | 4x+27=72-2x | | 6x+39=14x-25 | | 6x^2+49-45=0 | | 3[x-5]=9 |